Analisis Nilai-Nilai Karakter yang Terkandung Dalam Proses Kodifikasi Al-Qur’an - Musya Rifah; Achmad Abubakar; Hasyim Haddade (Intiqad: Jurnal Agama dan Pendidikan Islam, 2022)
This study discusses about history of the codification Qur'an, from the collection period to the completion of punctuation marks, analyzes the character values that stand out during the process, with the purpose that these values can be imitated by today's ummah. This type of research is (library research), with data sources from books, articles or journals related to the subject matter. The results showed that historically, there were many problems that occurred at that time, first, the rejection and concern of Abu Bakr and Zaid bin Thabit towards the collection of the Qur'an because of the absence of orders from the Prophet, secondly, during the time of Abu Bakr and Umar as a form of prudence, giving instructions and strict standards must be two witnesses, third, the period of Usman, set one standard manuscript, as a solution to the division of the Islamic ummah related to the problem of differences in qira'at, fourth, improvement of writing and punctuation due to the increasing needs of Muslims great attitude towards the Qur'an, while many of its adherents come from outside the Arabian peninsula. The author's analysis of the values of character education that can be imitated today from all the problems that occurred during the codification period are: the courage to express an opinion if it is the truth and for the benefit of the ummah, wise and humble attitude which is reflected in the leader of the community, obedience to the leader in kindness is a must, prioritizing deliberation as a way of resolving if there is a dispute, being critical of the situation and daring to take decisions if it is for the unity of the ummah.